The Existence Of Penjor Pan Balang Tamak In Karangasem - Suniada, I Gede (Bali Tourism Board, 2024)
Penjor symbolizes gratitude and appreciation for the blessings of the earth bestowed by the divine. Balinese Hindus believe that Mount Agung is the sacred residence of Hyang Bathara Putra Jaya, along with other gods and ancestors. In the village of Karangsari Karangasem, there is a Penjor that remains true to ancestral traditions, unchanged from what has been orally passed down by the village elders. This Penjor is known as Penjor Balang Tamak. It represents critical thinking, devotion, and an expression of thanks to Ida Sang Hyang Widhi Wasa. The use of this Penjor has been preserved through generations and has become an integral part of the community's identity. It is placed in the northwest corner of the Bale Agung, to the east of the Candi Bentar in the Pura Puseh courtyard, as a tribute to the Balang Tamak figure and a symbolic witness to the village council meetings (pesangkepan) held at Bale Agung.